VARIASI POLA VOKALISASI PADA TAKSONOMI ANAK JENIS ELANG-ULAR (Spilornis cheela) DI PKEK, GARUT, JAWA BARAT - Dermi, Devi Fauzia; Sedayu, Agung; Komala, Ratna (Bioma, 2017)
Crested serpent eagle (Spilornis cheela) is a bird of prey with distinctive of uniue vocal. Based on several studies mentioned that there are differences in vocalization at the level of subspecies and is often used to study the role vocalization defining the subspecies in taxonomy. This research aimed to determine the role variation of vocalization pattern in taxonomy on subspecies eagle. The research was conducted from May to September 2017 at Kamojang Eagle Conservation Center. The method used is descriptive method with continuous sampling technique. The samples was an adult eagle from three subspecies serpent eagle. The location of observation determined by purposive sampling with the provisions listening post is less than 5 meters until 30 meters. The data is collected at 7 am to 5 pm. Data were analyzed using sound analysis software. The data taken are fundamental frequency, maximum frequency (MinF), minimum frequency (MinF) and duration. Differences between subspecies were analyzed using Kruskal Wallis and Mann-Whitney U statistical test with SPSS 17.0. The result of the research is The vocalizations can be utilized in the subspecies eagle taxonomy of the species to complement the morphological data, marked by significantly different results on each parameter of vocalization between (Spilornis cheela malayensis) and (Spilornis cheela natunensis). MaxF significantly different in (Spilornis cheela malayensis) and (Spilornis cheela bido), (Spilornis cheela natunensis) and (Spilornis cheela bido).